Damage processes exhibited by WC-CO Composite in Rock Drilling. - Anacleto, Nathaniel M.
A study of the interaction of tungsten carbide-cobalt inserts with rocks and abrasive was carried out using an abrasive wear test and drop weight test. In both tests, it was shown that the major mechanism of wear loss is associated with microfracture and/or fragmentation of WC grains. The study has also revealed that wear of WC-Co depends on the hardness and abrasiveness of the rock or abrasive. The weight loss was found to be directly proportional to the number of blows during the drop weight test, while in the abrasive wear test, the weight loss was directly proportional to the hold down load the traverse length. An analysis of the results showed that the major wear process of the WC-Co inserts during rotary percussive drilling is impact damage and the contribution of sliding abrasion to the total wear is insignificant.
Keywords: Tungsten carbide-cobalt.